Characterization of high- and low-risk hepatocellular adenomas by magnetic resonance imaging in an animal model of glycogen storage disease type 1A - Roberta Resaz; Francesca Rosa; Federica Grillo; Luca Basso; Daniela Segalerba; Andrea Puglisi; Maria Carla Bosco; Luca Mastracci; Carlo E. Neumaier; Luigi Varesio; Alessandra Eva (The Company of Biologists, 2019)
Hepatocellular adenomas (HCAs) are benign tumors, of which the most serious complications are hemorrhage and malignant transformation to hepatocellular carcinoma (HCC). Among the various subtypes of HCA, the β-catenin-activated subtype (bHCA) is associated with greatest risk of malignant transformation. Magnetic resonance imaging (MRI) is an important tool to differentiate benign and malignant hepatic lesions, and preclinical experimental approaches may help to develop a method to identify MRI features associated with bHCA. HCAs are associated with various pathologies, including glycogen storage disease 1a (GSD1a). Here, we utilized a mouse model for GSD1a that develops HCA and HCC, and analyzed the mice in order to distinguish low-risk from high-risk tumors. Animals were scanned by MRI using a hepato-specific contrast agent. The mice were sacrificed after MRI and their lesions were classified using immunohistochemistry. We observed that 45% of the animals developed focal lesions, and MRI identified four different patterns after contrast administration: isointense, hyperintense and hypointense lesions, and lesions with peripheral contrast enhancement. After contrast administration, only bHCA and HCC were hypointense in T1-weighted imaging and mildly hyperintense in T2-weighted imaging. Thus, high-risk adenomas display MRI features clearly distinguishable from those exhibited by low-risk adenomas, indicating that MRI is a reliable method for early diagnosis and classification of HCA, necessary for correct patient management.